TRANSFORMASI ADAPTASI PENCIPTAAN SENI MOZAIK SEKUENSIAL ( STUDI KASUS HIKAYAT LEGENDA SANGKURIANG) - Anggakarti, Deden Maulana; Astuti, Marisa; Benyamin, M. Firdaus (Gorga : Jurnal Seni Rupa, 2024)
Traditional mosaic art has undergone substantial changes in its visual expression. One of them is the sequential mosaic art of the Legend of Sangkuriang in digital media, where its application uses a glass screen. The purpose of this study is to explore the influence of adaptation on the sequential mosaic art of the Sangkuriang Legend and its implications in contemporary culture. The research method used is a descriptive qualitative method that involves historical and technical studies on the development of mosaic art, digital mosaic design, and the process of digital adaptation with the content of the saga story of the Sangkuriang legend. Data collection techniques are in the form of documentation and literature studies. Data analysis was carried out with a descriptive qualitative approach to understand the impact of digital transformation and adaptation on mosaic art. The results of the study show that it creates a more dynamic and interactive visual experience. The creation of artworks allows artists to incorporate digital elements such as animation and dynamic visual effects in mosaic artwork. The positive response from visitors shows interest in innovation and a better understanding of the changing art of mosaic through digital technology. In conclusion, the sequential transformation of mosaic art in digital media is an important development in contemporary fine art. This opens up new opportunities for educational spaces, artistic expression, cultural promotion, and cultural heritage preservation. This research provides important insights into these changes and encourages further exploration in mosaic art in the ever-evolving digital age, especially in Indonesia.Keywords: transformation, mosaic, Sangkuriang, digital, cultureAbstrakSeni mozaik tradisional telah mengalami perubahan substansial dalam ekspresi visualnya. Salah satunya adalah seni mozaik sekuensial Legenda Sangkuriang dalam media digital, dimana penerapannya menggunakan layar kaca. Tujuan penelitian ini adalah untuk mendalami pengaruh adaptasi terhadap seni mozaik sekuensial Legenda Sangkuriang dan implikasinya dalam budaya kontemporer. Metode penelitian yang digunakan adalah metode kualitatif deskriptif yang melibatkan studi historis dan teknis tentang perkembangan seni mozaik, perancangan mozaik digital, dan proses adaptasi digital dengan konten cerita hikayat legenda Sangkuriang. Teknik pengumpulan data berupa dokumentasi dan studi pustaka. Analisis data dilakukan dengan pendekatan kualitatif deskriptif untuk memahami dampak transformasi dan adaptasi digital terhadap seni mozaik. Hasil penelitian menunjukkan menciptakan pengalaman visual yang lebih dinamis dan interaktif. Penciptaan karya seni memungkinkan seniman menggabungkan elemen-elemen digital seperti animasi dan efek visual yang dinamis dalam karya seni mozaik. Respons positif dari pengunjung menunjukkan minat terhadap inovasi dan pemahaman yang lebih baik tentang perubahan seni mozaik melalui teknologi digital. Kesimpulannya, transformasi seni mozaik sekuensial dalam media digital adalah perkembangan penting dalam seni rupa kontemporer. Ini membuka peluang baru untuk ruang pendidikan, ekspresi seni, promosi budaya, dan pelestarian warisan budaya. Penelitian ini memberikan wawasan penting tentang perubahan ini dan mendorong eksplorasi lebih lanjut dalam seni mozaik dalam era digital yang terus berkembang khususnya di Indonesia.Kata kunci : transformasi, mozaik, Sangkuriang, digital, budaya.Authors:Deden Maulana A : Universitas WidyatamaMarisa Astuti : Universitas WidyatamaM. Firdaus Benyamin : Universitas WidyatamaReferencesAnggakarti, D. M. (2023). TRANSFORMASI LEGENDA SANGKURIANG DALAM SEKUENSIAL MOZAIK DIGITAL. ICHES: International Conference on Humanity Education and Society, 2(1), 11.Busch, T., & Shepherd, T. (2014). Doing well by doing good? Normative tensions underlying Twitter™s corporate social responsibility ethos. Convergence, 20(3), 293“315. https://doi.org/10.1177/1354856514531533Devi, B. I. (2014). MOZAIK SEBAGAI MEDIA PENINGKATAN KEMAMPUAN MOTORIK HALUS ANAK TUNAGRAHITA RINGAN KELAS 1 SDLB-C SLB NEGERI 2 YOGYAKARTA. UNIVERSITAS NEGERI YOGYAKARTA.Hasnawati, H., & Anggraini, D. (2018). Mozaiksebagai Sarana Pengembangan Kreativitas Anak Dalam Pembelajaran Seni Rupamenggunakan Metode Pembinaan Kreativitas Dan Keterampilan. Jurnal PGSD, 9(2), 226“235. https://doi.org/10.33369/pgsd.9.2.226-235Hermawan Wicaksono, H., & Nur Wijayani, Q. (2024). Kritik Sosial Melalui Kesenian: Analisis Mahasiswa Universitas Trunojoyo Madura dalam Konteks Kontemporer. Harmoni: Jurnal Ilmu Komunikasi Dan Sosial, 2(1), 21“30. https://doi.org/10.59581/harmoni-widyakarya.v2i1.2296Murfianti, F., Sos, S., Med, M., & Kom, N. (2019). Hak Cipta Dan Karya Seni Di Era Digital Institut Seni Indonesia (Isi) Surakarta. 6867, 15.Nagy, P., & Koles, B. (2014). The digital transformation of human identity: Towards a conceptual model of virtual identity in virtual worlds. Convergence, 20(3), 276“292. https://doi.org/10.1177/1354856514531532Pasaribu, M. E., & Atmojo, W. T. (2023). Puzzle Sebagai Sumber Inspirasi Penciptaan Motif Batik. Gorga¯: Jurnal Seni Rupa, 12(1), 01. https://doi.org/10.24114/gr.v12i1.39438Revondya, F. P. (2011). Street Art Gallery Di Yogyakarta. 16“69. http://e-journal.uajy.ac.id/2223/Sherer, S. A., Meyerhoefer, C. D., & Peng, L. (2016). Applying institutional theory to the adoption of electronic health records in the U.S. Information and Management, 53(5), 570“580. https://doi.org/10.1016/j.im.2016.01.002Trantopoulos, K., Von Krogh, G., Wallin, M. W., & Woerter, M. (2017). External knowledge and information technology: Implications for process innovation performance. MIS Quarterly: Management Information Systems, 41(1), 287“300. https://doi.org/10.25300/MISQ/2017/41.1.15Yao, Q., Tang, H., Boadu, F., & Xie, Y. (2023). Digital Transformation and Firm Sustainable Growth: The Moderating Effects of Cross-border Search Capability and Managerial Digital Concern. Journal of the Knowledge Economy, 14(4), 4929“4953. https://doi.org/10.1007/s13132-022-01083-xYing-Yu, K. C., Yi-Long, J., & Yu-Hsien, W. (2016). Effect of Digital Transformation on Organisational Performance of SMEs: Evidence from the Taiwanese Textile Industry™s Web Portal. In Internet Research (Vol. 26, Issue 1).